Health policy experts’ perspectives on implementing mental health specialist video consultations in routine primary care: a qualitative interview study - Tönnies, Justus; Oeljeklaus, Lydia; Wensing, Michel; Hartmann, Mechthild; Friederich, Hans-Christoph; Haun, Markus W. (BMC health services research, 2021)
Many patients with mental disorders are treated by their general practitioner (GP). Innovative technology-based integrated care models (e.g., mental health specialist video consultations) have been proposed to facilitate access to specialist services in primary care settings. While perspectives of patients and providers have been examined, there is little insight into the perspectives of health policy experts on such models. The purpose of this study was to examine the perspectives of health policy experts on (1) current challenges for continuity of care, (2) anticipated benefits and barriers for implementation of mental health specialist video consultations along with (3) practical and regulative preconditions for sustained implementation in primary care.
Gesehen am 09.09.2021